Linguocognitive Features of Reflecting Different Emotions in Literary Texts - Sanatovna, Narzullaeva Dilnoza (International Journal on Integrated Education, 2023)
The article contains the description of different emotions of personages of fiction that reflects the culture, way of thinking, lifestyle and valuable norms of the language bearers. The aim of the article is to analyze linguocognitive features of describing emotional state of literary personages in fiction texts.